(untitled) (Journal of Medical & Health Sciences Review, 2025)
The effects of different dietary doses of organic selenium (Se) on the growth, body composition, and haematological parameters of silver carp were evaluated in a feeding experiment. The basal diet was supplemented with selenium at levels of 0.0, 0.5, 1, and 2 mgkg⁻¹. A total of 25 fish were randomly stocked into 500 L tanks using Recirculating Aquaculture System (RAS) technology and fed for ten weeks. Fish fed diets containing 0.5 mgkg⁻¹, 1 mgkg⁻¹, and 2 mgkg⁻¹ Se showed significantly higher weight gain, final body weight, and specific growth rate (p<0.05). The lowest growth values were observed in fish fed the basal diet. Survival rate was similar among all treatment groups, and no significant difference was observed in feed intake (p>0.05). Whole-body composition analysis revealed that fish fed 1 mgkg⁻¹ Se had significantly higher body moisture and protein levels on a dry weight basis (p<0.05). Fish receiving 2 mgkg⁻¹ Se had the highest fibre content, while those fed 0.5 mgkg⁻¹ had significantly higher ash content. Dietary selenium had no significant effect on fat content. Whole-body selenium concentrations increased significantly (p<0.05) with increasing dietary Se levels. Haematological data indicated that fish fed 0.5 mgkg⁻¹ and basal diets exhibited significantly higher haemoglobin and red blood cell counts (p<0.05). White blood cell counts were higher in fish fed basal and 2 mgkg⁻¹ diets, whereas lymphocyte percentages were higher in fish fed basal and 0.5 mgkg⁻¹ diets (p<0.05). Overall, the study concludes that dietary selenium supplementation benefits silver carp. Supplementation with organic selenium, particularly at 0.5–1 mgkg⁻¹, improved growth performance, whole-body protein content, selenium deposition, and certain haematological indicators. Therefore, the optimal dietary selenium level for silver carp is suggested to be between 0.5 and 1 mgkg⁻¹.